Cup blocks the precocious activation of the orb autoregulatory loop. - Li Chin Wong; Paul Schedl (PLoS ONE, 2011)
Translational regulation of localized mRNAs is essential for patterning and axes determination in many organisms. In the Drosophila ovary, the germline-specific Orb protein mediates the translational activation of a variety of mRNAs localized in the oocyte. One of the Orb target mRNAs is orb itself, and this autoregulatory activity ensures that Orb proteins specifically accumulate in the developing oocyte. Orb is an RNA-binding protein and is a member of the cytoplasmic polyadenylation element binding (CPEB) protein family. We report here that Cup forms a complex in vivo with Orb. We also show that cup negatively regulates orb and is required to block the precocious activation of the orb positive autoregulatory loop. In cup mutant ovaries, high levels of Orb accumulate in the nurse cells, leading to what appears to be a failure in oocyte specification as a number of oocyte markers inappropriately accumulate in nurse cells. In addition, while orb mRNA is mislocalized and destabilized, a longer poly(A) tail is maintained than in wild type ovaries. Analysis of Orb phosphoisoforms reveals that loss of cup leads to the accumulation of hyperphosphorylated Orb, suggesting that an important function of cup in orb-dependent mRNA localization pathways is to impede Orb activation.